Predictions of an ambient stable uranium and a superhard uranium - Wen, Xiaoshang; Zhang, Runqing; Li, Junzhao; Zhang, Jingyi; Zhang, Haijie; Dong, Huafeng; Wang, Renhai; Yang, Yujue; Wu, Fugen (Physical chemistry chemical physics : PCCP, 2025)
Uranium has significant applications in nuclear physics, nuclear engineering and medicine. Understanding its structure and fundamental properties is extremely important. Here, we found that the previous understanding of its structure may be wrong. Based on the evolutionary algorithm, we discovered three new structures of uranium at ambient pressure ( -U, 1̄-U and 3̄ -U). The -U has the lowest energy at zero pressure, rather than the reported -U in experiments. While they share similar structures, the key difference is that the -U structure has more different U-U bonds compared to -U, causing a decrease in symmetry. The calculation of the phonon dispersion curves and band structures has confirmed that -U, 1̄-U, 3̄ -U and -U are dynamically stable metal structures at ambient pressure. Interestingly, we found that the 3̄ -U structure is the hardest uranium (Vickers hardness ∼40.89 GPa), which is currently the only superhard and conductive material in the actinide series. On the one hand, 3̄ -U has the shortest bond length (2.667 Å) in the uranium system and its atomic interaction force is the strongest. On the other hand, due to it having the maximum shear modulus in the actinide series (Vickers hardness is proportional to shear modulus), 3̄ -U has the highest Vickers hardness. Moreover, the pressure-induced phase transition sequence of uranium was determined to be . This work not only deepens our understanding of stable uranium under ambient pressure, but also found a superhard uranium, which provides deeper and more comprehensive theoretical guidance for the applications of uranium.